Jurisprudence of the European court of human rights in the choice of precautionary measures in criminal proceedings: legal realities and perspectives - Романцова, Світлана Василівна; Романцова, С. В.; Романцова, Светлана Васильевна; Romantsova, Svitlana V.; Зіньковський, Ігор Петрович; Зіньковський, І. П.; Зиньковский, Игорь Петрович; Zinkovskyy, Ihor P.; Комісарчук, Руслан Васильович; Комісарчук, Р. В.; Комисарчук, Руслан Васильевич; Komisarchuk, Ruslan V.; et al. (Universidad del Zulia, 2020)
The article deals with the problems of application of the decisions of the European Court of Human Rights (ECHR) in the selection of precautionary measures in criminal cases in accordance with Ukrainian law. Since the procedural legislation of Ukraine is currently not perfect in the framework of the establishment and regulation of the application of precautionary measures, the decisions of the ECHR serve as an indispensable regulator of this issue. The objective of the work is to study the peculiarities of the application of the jurisprudence of the European Court of Human Rights in the selection of precautionary measures in criminal proceedings. The subject of the investigation is the jurisprudence of the ECHR in the context of the choice of precautionary measures in the criminal process. The research methodology included and combined the dialectical method, logical and legal method, analysis, synthesis. By way of conclusion, the study shows that the practice of the ECHR is mandatory to take into account not only the courts but also the investigators and prosecutors, who legally have the right to request the court to apply such precautionary measures.

У статті розглядаються проблеми застосування рішень Європейського суду з прав людини (ЄСПЛ) при обранні запобіжних заходів у кримінальних справах відповідно до законодавства України. Оскільки процесуальне законодавство України на сьогодні не є досконалим у рамках встановлення та регулювання застосування запобіжних заходів, рішення ЄСПЛ є неодмінним регулятором цього питання. Метою роботи є дослідження особливостей застосування судової практики Європейського суду з прав людини при виборі запобіжних заходів у кримінальному провадженні. Предметом розслідування є судова практика ЄСПЛ у контексті вибору запобіжних заходів у кримінальному процесі. Методологія дослідження включала та поєднувала діалектичний метод, логіко-правовий метод, аналіз, синтез. Як висновок, дослідження показує, що практика ЄСПЛ обов’язково має враховувати не лише суди, а й слідчі та прокурори, які за законом мають право вимагати від суду застосування таких запобіжних заходів.
Romantsova S. Jurisprudence of the European court of human rights in the choice of precautionary measures in criminal proceedings: legal realities and perspectives / S. Romantsova, I. Zinkovskyy, R. Komisarchuk, O. Balatska, L. Strelbitska // Cuestiones Políticas. - Vol. 38. - Issue 67. - Universidad del Zulia, 2020. - P. 443-458.
Keywords: European Court of Human Rights; European jurisprudence; precautionary measures; criminal process; legal reality of Ukraine; Європейський суд з прав людини; європейська юриспруденція; запобіжні заходи; кримінальний процес; правова реальність України; Research Subject Categories::LAW/JURISPRUDENCE